2022
DOI: 10.7759/cureus.32580
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Online Learning Among Undergraduate Medical Students of Eastern India: A Cross-Sectional Study

Abstract: BackgroundIn 2020 WHO declared the coronavirus disease 2019 (COVID-19) outbreak as a global pandemic. To flatten the curve of infection, a nationwide lockdown was declared by the Indian government. All the schools and colleges were shut for an indefinite period. Like all other streams, medical education also got severely hampered. Adapting themselves to the changing environment, teachers started using different teachinglearning methods and media to get across to the students. The objective of the research was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…A UK-based national survey among the 39 medical schools (2721 participants) revealed that common challenges to online teaching were family distractions (27%) and internet connection (22%), which were also the opinions of the FGD participants of our study [20]. The medical students of West Bengal, India, also responded in a cross-sectional descriptive study through an online questionnaire that the major challenges of online learning are internet connectivity issues (80%), family distractions (38%), and inconvenient timing of classes (20%) [21]. The findings favor the opinions of the participants in our focus group discussions.…”
Section: Resultsmentioning
confidence: 52%
“…A UK-based national survey among the 39 medical schools (2721 participants) revealed that common challenges to online teaching were family distractions (27%) and internet connection (22%), which were also the opinions of the FGD participants of our study [20]. The medical students of West Bengal, India, also responded in a cross-sectional descriptive study through an online questionnaire that the major challenges of online learning are internet connectivity issues (80%), family distractions (38%), and inconvenient timing of classes (20%) [21]. The findings favor the opinions of the participants in our focus group discussions.…”
Section: Resultsmentioning
confidence: 52%
“…4 and on undergraduate medical students of Eastern India. 8 The major disadvantage of technical problem during online study could be because the technology was relatively newer at the time of data collection and has advanced tremendously within these two years. Meanwhile, most of the students categorized themselves as moderate level in IT skill which is a hopeful information, as it opens the door to incorporate the VL into dental curriculum with relative ease.…”
Section: Discussionmentioning
confidence: 99%
“…Developed internet connections, synchronised live streaming settings, and technological advances have made e-learning feasible. The national medical commission in India advocated for online classes due to the emergence of the pandemic in medical colleges all across the country [17]. In their way of adapting themselves to the changed surrounding, the teachers initiated utilisation of online teaching-learning media and methods to facilitate education to the students.…”
Section: Technoarete Transactions On Applications Of Information and ...mentioning
confidence: 99%